Hak Ibu Bapa terhadap Nafkah dalam Perundangan Islam (Kanun: Jurnal Undang-undang Malaysia, 2012)
This article will discuss parental right to maintenance under Islamic law. In order to preserve familial harmony, children too have to exercise certain rights and carry out certain obligations towards their parents. As such, this article examines the current provisions available under Islamic Law in Malaysia. Further, a comparative analysis of the provisions applied in West Asian countries to those in Malaysia is also sought. A close perusal of the provisions is deemed necessary to enquire into whether such provisions are adequate to protect parental rights to maintenance. Hence, parental rights to maintenance will be carried out and not neglected. Should the adverse happens, the available provisions will provide the necessary remedies.Keywords: maintenance, parental right, Islamic law